2011
DOI: 10.1371/journal.pone.0023656
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Neuron Deficit As An Idiopathic Generalized Epilepsy Mechanism: The Role Of BRD2 Haploinsufficiency In Juvenile Myoclonic Epilepsy

Abstract: Idiopathic generalized epilepsy (IGE) syndromes represent about 30% of all epilepsies. They have strong, but elusive, genetic components and sex-specific seizure expression. Multiple linkage and population association studies have connected the bromodomain-containing gene BRD2 to forms of IGE. In mice, a null mutation at the homologous Brd2 locus results in embryonic lethality while heterozygous Brd2+/− mice are viable and overtly normal. However, using the flurothyl model, we now show, that compared to the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 64 publications
4
72
0
Order By: Relevance
“…However, the pathophysiologic mechanisms explaining the relationship between GGE and thalamic volume loss are still unknown. One possible mechanism might relate to genetic variation in bromodomain containing 2, reported in JME patients39 which has been found to lead to γ‐aminobutyric acid (GABA)ergic neuron deficit found in mice40; this might associate with thalamic volume loss as reported here.…”
Section: Discussionmentioning
confidence: 64%
“…However, the pathophysiologic mechanisms explaining the relationship between GGE and thalamic volume loss are still unknown. One possible mechanism might relate to genetic variation in bromodomain containing 2, reported in JME patients39 which has been found to lead to γ‐aminobutyric acid (GABA)ergic neuron deficit found in mice40; this might associate with thalamic volume loss as reported here.…”
Section: Discussionmentioning
confidence: 64%
“…Previous research on epilepsy suggests that females experience more idiopathic generalized epilepsy (IGE) than males (Camfield et al, 2013; Camfield and Camfield, 2009; Valentin et al, 2007). IGE is familial related and some genetic causes of IGE are known (e.g., mutations on the sodium channel and GABA receptors) (Velisek et al, 2011; Amiet et al, 2008). It has been suggested that some of these same genetic causes of epilepsy – particular those that implicate genetic mutations on sodium channels –may represent ASD phenocopies that deserve further exploration (Amiet et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous Brd2 +/− mice are viable and overtly normal, but have a decreased tonic-clonic seizure threshold compared to Brd2 +/+ wild type mice. Further, anatomical analysis of the brain shows that the number of GABAergic neurons in the neocortex and the striatum of Brd2 +/− mice are decreased, compared to those in Brd2 +/+ mice [52]. These findings indicate that an insufficiency of BRD2 protein is associated with a decrease in the number of neuronal cells required for critical brain structures.…”
Section: Basic Functions Of Brd2 and Brd3mentioning
confidence: 99%